Strategic aspects of reaction time in world-class sprinters - Collet, C. (1999)
Simple reaction time (RT) is defined as the time duration following the initiation of a stimulus and the resultant first observable response. For sprinters, RT to a start should be especially important, as this may determine the outcome of the race. The aim of this study was to investigate whether sprinters (from 100 to 400 m) try to anticipate the starter's shot within the false start limit (100 msec. after the shot). Subjects were male sprinters who have reached the final of a sprint event in World Championships or Olympic Games. Analysis indicated that RT to the starting shot plays a role in the eight finalists' strategy throughout an event (requiring a total of four sprints). Four characteristics of the strategic aspects of RT were found: (i) Increased mean RT from short dashes to longer sprints (from 60 m indoor, to 100 m, 200 m, and 400 m); (ii) RT values increase as a function of race length, i.e., the RT of the first sprinter in a 4 x 100-m relay is no different from that of a 400-m sprinter; conversely, RT of the first relay sprinter in a 4 x 400-m, i.e., a 1600-m race, is significantly different from RT in a 400-m race; (iii) RT decreases from the heats to the final for the eight finalists; (iv) Decreased RT is not observable in less experienced sprinters through the qualifying rounds (junior 18- or 19-yr.-old sprinters, taking part in their own World Championships). RT must be considered a skill dependent upon experience and learning and is associated with race length. The shorter the race, the more important the RT is for the final performance (both time and place), so sprinters try to decrease RT in the shorter dashes (60 m and 100 m). In the longer sprint races (4 x 400-m relay) they are content to respond to the shot. Intermediate distance races elicit intermediate values of RT. Such behavior could be explained by the importance of RT throughout the factors which influence sprint performance and by reference to allocation of concentration resources and expenditure. Percept Mot Skills 1999 Feb;88(1):65-75